High alkaline resistance of benzyl-triethylammonium functionalized anion exchange membranes with different pendants. (April 2018) - Ye, Niya; Xu, Yixin; Zhang, Dengji; Yang, Yunfei; Yang, Jingshuai; He, Ronghuan
Graphical abstract: Highlights: Free radical polymerization of novel polymers with different aromatic pendants. The AEM containing p -ethyl phenol groups exhibits excellent tolerance to alkali. Paraethyl phenol protecting the AEMs from the nucleophilic attack is evidenced. Abstract: Polymers were synthesized by polymerization of 4-vinylbenzyl chloride with three kinds of aromatic monomers, respectively. Quaternization of these polymers with triethylamine were performed to fabricate associated anion exchange membranes (AEMs) possessing different pendants. The obtained AEMs showed excellent stability in alkaline solutions at elevated temperature and exhibited conductivities of 32.6–39.5 mS cm −1 in water at 80 °C. In particular, the AEM having a pendant of p -ethyl phenol could maintain the initial conductivity of 89% after immersed in 1 M KOH at 80 °C for 1000 h. Even soaked in 8 M KOH solution at 80 °C for 24 h, this AEM still exhibited a conductivity of 26.4 mS cm −1 at 80 °C, about 80% of its original conductivity was remained. However, the rest of prepared AEMs showed significant decline in conductivity. We studied the tolerance of the prepared AEMs to 8 M KOH at 80 °C in the presence of p -ethyl phenol with a concentration of 0.025 M. It is found that the stability of all the AEMs was obviously enhanced, about 70–90% of the initial conductivity was retained. This result suggests an effective strategy to improve the alkaline stability of the AEMs.